(1420) An economy wide model for simulating the behavior of the Egyptian economy نموذج اقتصادي شامل لمحاكاة سلوك الاقتصاد المصري - Khorshid, Motaz; Osman, Osman M. (2018)
In this paper we formulate and implement an economywide model, based on the social accounting framwork, for analyzing the performance of the Egyptian economy in the medium term.